STRATEGI KOMUNIKASI EMOTIF DALAM TUTURAN DAKWAH USTAZ HILMAN AL FAUZI: KAJIAN SOSIOPRAGMATIK - Lisna Lisna; Hari Windu Asrini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The digital media transformation encourages preachers to package religious lectures emotively to build social and emotional closeness with the audience. This descriptive qualitative study using a sociopragmatic approach aimed to describe Ustaz Hilman Al Fauzi's emotive communication strategies on the Taubat Nasuha YouTube channel and explain how speech contexts influence their usage. Data were gathered through non-participatory observation, verbatim transcription, and note-taking, then analyzed using the Miles, Huberman, and Saldaña interactive model grounded in Aristotelian rhetoric, Searle's speech acts, and Hymes' SPEAKING model. Results identified six primary emotive communication strategies: instilling hope, fostering reassurance, providing spiritual motivation, strengthening religious conviction, employing life analogies, and incorporating textual legitimacy from the Qur'an and Hadith. These strategies integrate psychological and religious reinforcement through a synthesis of ethos, pathos, and logos. The main conclusion confirms that digital preaching effectiveness depends heavily on the preacher's skill in aligning emotive language choices with the audience's social context and emotional state. ABSTRAK Transformasi media digital mendorong pendakwah mengemas ceramah keagamaan secara emotif untuk membangun kedekatan hubungan sosial dan emosional dengan audiens. Penelitian kualitatif deskriptif berpendekatan sosiopragmatik ini bertujuan mendeskripsikan strategi komunikasi emotif Ustaz Hilman Al Fauzi pada kanal YouTube Taubat Nasuha serta pengaruh konteks tuturan terhadap penggunaannya. Pengumpulan data dilakukan melalui teknik simak bebas libat cakap, transkripsi verbatim, dan pencatatan, yang dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña dengan landasan retorika Aristoteles, tindak tutur Searle, serta komponen tutur Hymes. Hasil penelitian menemukan enam strategi komunikasi emotif utama, meliputi membangun harapan, menumbuhkan ketenangan, memberikan motivasi spiritual, memperkuat keyakinan religius, menggunakan analogi kehidupan, serta menyertakan legitimasi dalil Al-Qur'an dan hadis. Strategi tersebut terintegrasi ke dalam dimensi penguatan psikologis dan religius melalui perpaduan ethos, pathos, dan logos. Simpulan utama menegaskan bahwa efektivitas dakwah digital sangat ditentukan oleh kejelian pendakwah dalam menyelaraskan pilihan strategi bahasa emotif dengan konteks sosial dan kondisi emosional jamaah.